Adsorption of sodium dodecyl benzene sulfonate onto carbonate rock: Kinetics, equilibrium and mechanistic study. Issue 5 (4th May 2018) - Hemmati, Nassim; Tabzar, Amir; Ghazanfari, Mohammad Hossein
ABSTRACT: In this study, kinetics, equilibrium, and mechanisms of SDBS adsorption onto carbonate rock in presence/absence of alkaline/electrolyte, which is not well discussed in the available literature, is analyzed through batch experiments. Analysis of kinetic data showed that adsorption rate of SDBS onto carbonate is controlled by both boundary layer and intraparticle diffusion, also adsorption kinetics meets pseudo second-order model. The coefficient of kinetic model is a linear function of initial and equilibrium concentrations. The adsorption isotherm experiences four distinct regions, with a rising trend in the first regions until reaching to a maximum after which decreases slightly, as the fourth region, due to micellar exclusion. The prevailing mechanisms in other regions were also discussed. Presence of alkaline changes adsorption mechanisms, so that adsorption isotherm matches well with the Langmuir model, while presence of electrolyte does not change the adsorption mechanisms, but it lessens repulsion between surfactant heads which results in a slight reduction in amount of CMC. A new three-parameter equilibrium model is presented which considers all prevailing mechanisms, and matches properly with obtained experimental data, especially the decreasing trend of fourth region which is very difficult to predict along with other regions using a unique isotherm model. GRAPHICAL ABSTRACT: